ANALYSIS PARACETAMOL IN "JAMU PEGAL LINU" POWDER - Fanani, Ferry; Yunitasari, Norainny (Indonesian Journal for Health Sciences, 2025)
The addition of BKO (Chemical Drug Ingredients) to traditional medicines is no longer commonplace. This condition is raises serious health concerns if it is allowed to continue because it can cause damage to body organs, especially liver damage. The purpose of this study was to test whether traditional medicines (“jamu pegal linu”) sold at Pasar Tingkat Lamongan contain paracetamol or not. This is because this type of traditional medicine is widely sold in this market and has never been tested for the presence of BKO. The traditional medicine samples studied have criteria that are not listed the composition of the ingredients. The test for the presence of BKO (paracetamol) uses two methods, namely the color test by reacting with iron (III) chloride reagent and the TLC test. The results of the study showed that 1 out of 4 samples studied contained paracetamol. For further research related to the TLC test for the presence of paracetamol in traditional medicines, it is better not to use only one type of eluent comparison